Salt-melt synthesis of B2O3, P2O5 and V2O5 modified high-alumina mullite nanocomposites with promising photoluminescence properties. (3rd October 2017) - Kool, Arpan; Thakur, Pradip; Bagchi, Biswajoy; Hoque, Nur Amin; Banerjee, Somtirtha; Das, Sukhen
Abstract: High-alumina mullite (Al4.8 Si1.2 O9.6 ) nanowhiskers have been prepared by mechano-chemical activation of Al2 (SO4 )3 –Na2 SO4 molten salt mixture in the presence of B2 O3, P2 O5 and V2 O5 as additives. Thermal evolution of the precursors has been studied by differential thermal analyzer and thermogravimetric analyzer (DTA-TG). The effect of additives on the phase formation and morphology of mullite is investigated using x-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and field emission scanning electron microscope (FESEM). Mullite whiskers with submicron sized length and diameter in the nanoscale range were obtained after calcining at 1000 °C. These nanowhiskers decomposed when sintered at 1400 °C with consequent formation of dense alumina platelets. Owing to formation of defect related structures of mullite, UV photoluminescence peaks for mullite reflected at 285, 298, 310, 325, 347, 362 and 379 nm while visible photoluminescence peaks appeared at 407, 424, 436 and 460 nm.